GITIMH3 94107 Complex Numbers Page 1

Introducton
20/10/98
Terms:
C.N Complex Number
C.C.N Conjugate Complex Number
To Solve Equations Such As: x
2
= ÷ 1
- We define the symbol ‘i’ such that: 1 i ÷ = i.e. i
2
= ÷ 1
- ‘i’ is called the imaginary number.
So x
2
= ÷ 1 can be written as:
x
2
= ÷ 1
x
2
= i
2
x = ± i
Forth Number System:
- A number ‘i.y’ is a pure imaginary number.
- A number ‘x’ is a pure real number.
- A number ‘x + i.y’ is a complex number.
A Complex Number
Equation: Z = x + i.y
Z = Complex number
x = Real function of the C.N = R(Z)
y = Imaginary function of the C.N = I(Z)
Conjugate of a Complex Number
Equation: y . i x Z ÷ =

Z
= Conjugate complex number
x = Real function of C.C.N = ( )
Z R
y = Imaginary function of C.C.N = ( )
Z I
Luke Cole Page 1
Note:
Complex numbers do not express
magnitude, however they express magnitude
and direction (Vector).
Note:
‘y’ is real, it’s ‘i’ that makes it
imaginary.
GITIMH3 94107 Complex Numbers Page 2
Operations
20/10/98
Sum of Complex Numbers:
Equation: (a + i.b) + (c + i.d) = (a + c) + i(b + d)
Proof:
(a + i.b) + (c + i.d) = 0
a + c + i.b + i.d = 0
(a + c) + i(b + d) = 0
Subtraction of Complex Numbers:
Equation: (a + i.b) – (c + i.d) = (a – c) + i(b – d)
Proof:
(a + i.b) – (c + i.d) = 0
a + i.b – c – i.d = 0
(a – c) + i(b – d) = 0
Product of Complex Numbers:
Equation: (a + i.b)(c + i.d) = (a.c – b.d) + i(a.d + b.c)
Proof:
(a + i.b)(c + i.d) = 0
a.c + i.a.d + i.b.c + i
2
.b.d = 0
Since i
2
= – 1:
(a.c – b.d) + i(a.d + b.c) = 0
Division of Complex Numbers:
Equation:
2 2 2 2
d c
d . a c . b
. i
d c
d . b c . a
d . i c
b . i a
+
÷
+
+
+
=
+
+
Proof:
0
d . i c
b . i a
=
+
+
0
id c
d . i c
d . i c
b . i a
=
÷
÷
×
+
+
0
d . i d . c . i d . c . i c
d . b . i c . b . i d . a . i c . a
2 2 2
2
=
÷ + ÷
÷ + ÷

2 2 2 2
d c
d . a c . b
. i
d c
d . b c . a
d . i c
b . i a
+
÷
+
+
+
=
+
+
Luke Cole Page 2
GITIMH3 94107 Complex Numbers Page 3
Ordered Pairs Operations:
Equation: (a, b) + (c, d) = (a + c, b + d)
Equation: (a, b) – (c, d) = (a – c, b – d)

Equation: (a, b) × (c, d) = (a.c – b.d, a.d + b.c)
Equation:
( )
( )
2 2 2 2
d c
ad c . b
,
d c
d . b c . a
d , c
b , a
+
÷
+
+
=
Equation: (a, b) = (c, d) iff, a = c, b = d
Equation: k(a, b) = (k.a, k.b)
Luke Cole Page 3
GITIMH3 94107 Complex Numbers Page 4
Solving Square Roots and Quadratic’s
20/10/98
Square Roots:
E.g. i . 12 5 +
A
i . 12 5 +
= a + i.b
= (a + i.b)
2
= a
2
– b
2
+ 2.i.a.b
So, 5 = a
2
– b
2
…(1)
12 = 2.a.b …(2)
(2) ¬
a
6
b =
…(3)
Sub (3) into (1)
2
2
a
6
a 5 |
.
|

\
|
÷ =
0 = a
4
– 5.a
2
– 36
0 = (a
2
– 9)(a
2
+ 4)
a = ±3 & 4 a ÷ ± =
Since we are solving for ‘x’ a real number > 0
a = 3
Sub a = 3 into (2)
b = 2
Sub a = 3 & b = 2 into Question
i . 12 5 + = a + i.b
= 3 + 2.i
Quadratic’s:
E.g. Find the roots of x
2
+ x + 1 = 0
A Use the quadratic formula
Roots,
2
3 1
x
÷ ± ÷
=
Since i
2
= – 1
i . 3 1 . 3 3 = ÷ = ÷

2
i . 3 1
x
± ÷
=
Luke Cole Page 4
Note:
Because the square root is ‘+’, i.e. a > 0,
therefore one answer. If the square root was
‘±’, i.e. a = IR therefore two answers.
GITIMH3 94107 Complex Numbers Page 5
The Argand Diagram
23/10/98
A complex number (Z = x + i.y) can be expressed as a point, but in turn is a vector with
magnitude and direction.


Distance OP:
- Called the modulus of the complex number.
- Denoted by: r = |Z| = mod Z = |x + i.y|
Equation:
2 2
y x Z + =
|Z| = Modulus of Z
x = R(Z)
y = I(Z)
ZPOM:
- Called the argument (or amplitude) of the complex number.
- Denoted by: u = arg Z = arg (x + i.y)
- Domain: ÷ t < u s t
Equation: arg Z = tan
-1
(y/x)
arg Z = ZPOM (÷ t < u s t)
y = I(Z)
x = R(Z)
Modulus-Argument (Vector) form of a Complex Number:
Equation: Z = r(cos u + i.sin u) = r.cis u
Z = Complex number
r = Modulus of complex number
u = Argument of complex number (÷ t < u s t)
Proof:
Z = x + i.y …(1)
x = r.cos u …(2)
y = r.sin u …(3)
Sub (2) & (3) into (1):
Z = r.cos u + i.r.sin u
Z = r(cos u + i.sin u) Abbreviated, Z = r.cisu
Luke Cole Page 5
y P
O M x
x ¬ Real Axis
y ¬ Imaginary Axis
O ¬ Origin
P ¬ (x, y)
ZPOM ¬ u
OP ¬ r
MP ¬ r.sinu = y
OM ¬ r.cosu = x
GITIMH3 94107 Complex Numbers Page 6
Operations
27/10/98
Note:
- If the u’s are out side the domain then ± 2.t
Equation: cos (÷ u) = cos u & sin (÷ u) = ÷ sin u
Product of Mod-Arg Complex Numbers:
Equation: Z
1
.Z
2
.….Z
n
= r
1
.r
2
.….r
n
.cis (u
1
+ u
2
+ …+ u
n
)
Z1 = 1
st
complex number
Z2 = 2
nd
complex number
Zn = n
th
complex number
r1 = 1
st
modulus of complex number
r2 = 2
nd
modulus of complex number
rn = n
th
modulus of complex number
u1 = 1
st
argument of complex number (÷ t < u s t)
u2 = 2
nd
argument of complex number (÷ t < u s t)
un = n
th
argument of complex number (÷ t < u s t)
Proof:
Let, Z1 = r1(cos u1 + i.sin u1) …(1)
Z2 = r2(cos u2 + i.sin u2) …(2)
Now (1) × (2):
Z1.Z2 = r1.r2(cos u1 + i.sin u1)(cos u2 + i.sinu2)
Z1.Z2 = r1.r2.cis (u1 + u2) …[1]
Generalising:
Z1.Z2.….Zn = r1.r2.….rn.cis (u1 + u2 + …+ un)
Equation: |Z
1
.Z
2
| = |Z
1
|.|Z
2
|
Z1 = 1
st
modulus of complex number
Z2 = 2
nd
modulus of complex number
Proof:
From [1]:
Z1.Z2= r1.r2.cis (u1 + u2)
|Z1.Z2| = |r1.r2.cis (u1 + u2)|
=
( )
2 1
2 2
2
2
1
cis . r . r u + u
= r1.r2
= |Z1|.|Z2|
Equation: arg Z
1
.Z
2
= arg Z
1
+ arg Z
2
arg Z1 = 1
st
argument of complex number (÷ t < u s t)
arg Z2 = 2
nd
argument of complex number (÷ t < u s t)
Luke Cole Page 6
GITIMH3 94107 Complex Numbers Page 7
Division of Mod-Arg Complex Numbers:
Equation:
( )
2 1
2
1
2
1
cis .
r
r
Z
Z
u ÷ u =
Z1 = 1
st
complex number
Z2 = 2
nd
complex number
r1 = 1
st
modulus of complex number
r2 = 2
nd
modulus of complex number
u1 = 1
st
argument of complex number (÷ t < u s t)
u2 = 2
nd
argument of complex number (÷ t < u s t)
Proof:
Let, Z1 = r1(cos u1 + i.sin u1) …(1)
Z2 = r2(cos u2 + i.sin u2) …(2)
Now (1) ÷ (2):
( )
( )
2 2 2
1 1 1
2
1
sin . i cos r
sin . i cos r
Z
Z
u + u
u + u
=
( )
( )
2 2
2 2
2 2 2
1 1 1
2
1
sin . i cos
sin . i cos
sin . i cos r
sin . i cos r
Z
Z
u ÷ u
u ÷ u
×
u + u
u + u
=

( )
2 1
2
1
2
1
cis .
r
r
Z
Z
u ÷ u =
…[2]
Equation:
2
1
2
1
Z
Z
Z
Z
=
Z1 = 1
st
modulus of complex number
Z2 = 2
nd
modulus of complex number
Proof:
From [2]:
( )
2 1
2
1
2
1
cis .
r
r
Z
Z
u ÷ u =
( )
2 1
2
2
1
2
1
cis .
r
r
Z
Z
u ÷ u =
= ( )
2 1
2
2
2
2
1
cis .
r
r
u ÷ u
=
2
1
r
r
=
2
1
Z
Z
Luke Cole Page 7
GITIMH3 94107 Complex Numbers Page 8
Equation: 2 1
2
1
Z arg Z arg
Z
Z
arg ÷ = |
.
|

\
|
arg Z1 = 1
st
argument of complex number (÷ t < u s t)
arg Z2 = 2
nd
argument of complex number (÷ t < u s t)
Powers of Mod-Arg Complex Numbers:
Equation: Z
n
= r
n
.cis (n.u)
Z = Complex number
r = Modulus of complex number
u = Argument of complex number (÷ t < u s t)
n = Integer
De Moivres Theorem
Equation: (cos u + i.sin u)
n
= cos (n.u) + i.sin (n.u)
(cos u ÷ i.sin u)
n
= cos (n.u) ÷ i.sin (n.u)
Proof:
Case 1: ‘n’ is a positive integer
Prove true for n = 1
LHS = (cos u + i.sin u)
1

= cos u + i.sin u
= RHS
Assume true for n = k
(cos u + i.sin u)
k
= cos (k.u) + i.sin (k.u)
Prove true for n = k + 1
(cos u + i.sin u)
k + 1
= cos [(k + 1)u] + i.sin [(k + 1)u]
LHS = (cos u + i.sin u)
k + 1
= (cos u + i.sin u)[cos (k.u) + i.sin (k.u)]
= cos [u + (u.k)] + i.sin [u + (u.k)]
= RHS
If true for n = k, then true for n = k + 1, but is true for n = 1, n = 2 and so on
True for all positive ‘n’
Case 2: ‘n’ is a negative integer
Let n = ÷ m where ‘m’ is a positive integer
(cos u + i.sin u)
n
= (cos u + i.sin u)
÷ m
=
( ) ( ) u + u . m sin . i . m cos
1
=
( ) ( )
( ) ( )
( ) ( ) u ÷ u
u ÷ u
×
u + u . m sin . i . m cos
. m sin . i . m cos
. m sin . i . m cos
1
= cos (m.u) ÷ i.sin (m.u)
= cos (÷ m.u) + i.sin (÷ m.u)
= cos (n.u) + i.sin (n.u)
True for all negative integer values of ‘n’
Luke Cole Page 8
GITIMH3 94107 Complex Numbers Page 9
Solving C.N
To Solve sin
n
u and/or cos
n
u in Terms of Multiples of u:
- Use the following equations to derive the answer
Equation: Z
n
+ Z
÷ n
= 2.cos (n.u)
Z
n
÷ Z
÷ n
= 2.i.sin (n.u)
Proof:
Let, Z = cos u + i.sin u
So, Z
n
= cos (n.u) + i.sin (n.u)
Z
÷ n
= cos (n.u) ÷ i.sin (n.u)
Z
n
+ Z
÷ n
= [cos (n.u) + i.sin (n.u)] + [cos (n.u) ÷ i.sin (n.u)] = 2.cos (n.u)
Z
n
÷ Z
÷ n
= [cos (n.u) + i.sin (n.u)] ÷ [cos (n.u) ÷ i.sin (n.u)] = 2.i.sin (n.u)
E.g. Express cos
3
u in terms of multiples of u
A Since, Z
n
+ Z
÷ n
= 2.cos (n.u) …(1)
Now, ( )
3
3
Z
1
Z cos . 2 |
.
|

\
|
+ = u
3
3 3
Z
1
Z
1
Z
2
Z . 2 Z Z cos . 8 + + + + + = u
|
.
|

\
|
+ + |
.
|

\
|
+ = u
Z
1
Z 3
Z
1
Z cos . 8
3
3 3
…(2)
Sub (1) into (2)

( ) u + u = u cos .
4
3
. 3 cos .
4
1
cos
3
To Solve sin (n.u) and/or sin (n.u) in Terms of cos u and sin u:
- Expanding (cos u + i.sin u)
n
and equating real and imaginary parts
E.g. Express cos (3.u) in terms of cos u and sin u
A Let, c = cos u & s = sin u
(c + i.s)
3
= (c + i.s)(c + i.s)(c + i.s)
= …
= c
3
÷ 3.c.s
2
+ i(3.c
2
.s ÷ s
3
)
cos (3.u) = c
3
÷ 3.c.s
2

Luke Cole Page 9
GITIMH3 94107 Complex Numbers Page 10
Roots of C.N
30/10/98
Graphing:
- Modulus of all roots (radius of circle) = r
1/n
- The first root is plotted by finding the argument for the first root, then the other
roots are equally spaced around circle with an angle between them = 360°/n
Finding Roots:
- Z
n
= a + i.b has ‘n’ roots on a circle with radius ‘r’.
Equation: |
.
|

\
| t + u
n
. k . 2
cis . r
n
1
r = Modulus of Z
n = ‘n’ roots
u = Argument of Z
k = 0, 1, 2, …, (n – 1)
Proof by Example:
E.g. Find the cube root of ÷ 1
A If Z is the cube root of ÷ 1 then
Z
3
+ 1 = 0
(Z + 1)(Z
2
– Z + 1) = 0
Z = ÷ 1 &
2
i . 3 1
Z
±
=
OR
A We Write
÷ 1 = cos t + i.sin t
Generalising this expression, add 2.k.t to the arg (÷ 1)
÷ 1 = cos (t + 2.k.t) + i.sin (t + 2.k.t) Where, k = 0, 1, 2
Now let the required cube root be
R(cos o + i.sin o)
( ) ( ) ( ) o + o = t + t + t + t sin . i cos R . k . 2 sin . i . k . 2 cos
3
cos (t + 2.k.t) + i.sin (t + 2.k.t) = R
3
[cos (3.o) + i.sin (3.o)]
Equating the LHS with RHS
R = 1 &
3
. k . 2 t + t
= o
Cube roots are given by
Z = R(cos o + i.sin o)
|
.
|

\
| t + t
+ |
.
|

\
| t + t
=
3
. k . 2
sin . i
3
. k . 2
cos Z Where, k = 0, 1, 2
Luke Cole Page 10
GITIMH3 94107 Complex Numbers Page 11
When, k = 0
i .
2
3
2
1
Z
1
+ =
When, k = 1
Z2 = ÷ 1
When, k = 2
i .
2
3
2
1
Z
3
÷ =
When, k = …, ÷2, ÷1, 3, 4, … the angles become the same as when k = 0, 1, 2.
These three roots lie on a circle of radius 1 and the arguments are:
arg Z1 = 60°
arg Z2 = 180°
arg Z3 = ÷ 60°



Luke Cole Page 11
y
Z
1
Z
2
1 x
Z
3
GITIMH3 94107 Complex Numbers Page 12
Properties of C.N and C.C.N
5/11/98



Equation: ¦Z¦=|
Z
=
2 2
y x +
Equation: arg Z = ÷ arg Z
Equation: Z.
Z
= x
2
+ y
2
= |Z|
2
= |
Z

2
Equation: Z +
Z
= 2.x
Equation: Z ÷
Z
= 2.i.y
Equation:
2 1 2 1
Z Z Z Z ± = ±
Equation:
2 1 2 1
Z . Z Z . Z =
Equation:
2
1
2
1
Z
Z
Z
Z
= |
.
|

\
|
Equation:
2
1
Z
Z
Z =
÷
Luke Cole Page 12
y
¦Z¦
y
u x x
÷ u
÷ y
| Z
GITIMH3 94107 Complex Numbers Page 13
The Complex Roots of Unity
12/11/98
- The complex root of unity has the equation Z
n
= 1 with ‘n’ roots and a 1 unit radius
(‘n’ is a positive integer)
- If ‘n’ is odd, there is one real root, Z
1
= 1, and (n – 1) complex roots occurring in
conjugate pairs
- If ‘n’ is even, there is two real roots, Z
1
= 1 & Z
2
= ÷ 1 and (n – 2) complex roots
occurring in conjugate pairs
- The roots of Z
n
= 1 are expressed: 1 , e, e
2
, … , e
n ÷ 1

Showing Roots are in Conjugate Pairs:
The equation Z
5
= 1 has roots:
Z1 = 1
5
. 2
sin . i
5
. 2
cos Z
2
t
+
t
=
5
. 4
sin . i
5
. 4
cos Z
3
t
+
t
=
5
. 6
sin . i
5
. 6
cos Z
4
t
+
t
=
5
. 8
sin . i
5
. 8
cos Z
5
t
+
t
=
Let, Z2 = e
So,
5
. 4
sin . i
5
. 4
cos Z
3
t
+
t
=
|
.
|

\
| t
+ |
.
|

\
| t
=
5
. 2
. 2 sin . i
5
. 2
. 2 cos Z
3
2
3
5
. 2
sin . i
5
. 2
cos Z |
.
|

\
| t
+
t
=
Z3 = e
2
Similarly, Z4 = e
3
& Z5 = e
4
Luke Cole Page 13
GITIMH3 94107 Complex Numbers Page 14
Also,
5
. 6
sin . i
5
. 6
cos Z
4
t
+
t
=
|
.
|

\
| t
÷ t + |
.
|

\
| t
÷ t =
5
. 4
. 2 sin . i
5
. 4
. 2 cos Z
4
5
. 4
sin . i
5
. 4
cos Z
4
t
÷
t
=
3 4
Z Z =
|
.
|

\
| t
÷ + |
.
|

\
| t
÷ =
5
. 2
. 2 sin . i
5
. 2
. 2 cos Z
4
2
4
5
. 2
sin . i
5
. 2
cos Z
÷
|
.
|

\
| t
+
t
=
Z4 = e
÷ 2
Here,
2
3 4
Z Z
÷
e = =
Similarly,
1
2 5
Z Z
÷
e = =
Sum of roots:
Equation: 1 + e + e
2
+ … + e
n ÷ 1
= 0
Proof:
For, Z
n
= 1
Sum of roots:
Sum of roots =
n
1 n
Z of t Coefficien
Z of t Coefficien
÷
÷
Since coefficient of Z
n ÷ 1
= 0:
1 + e
n
+ e
2
+ … + e
n ÷ 1
= 0
For More Information of Sum of Roots See Polynomials
Luke Cole Page 14
GITIMH3 94107 Complex Numbers Page 15
Factorisation over the Complex Field
17/11/98
We Can Factorise Z
n
÷ 1, Z
n
+ 1 & Z
n
+ Z
n ÷ 1
+ Z
n ÷ 2
+ … + 1
Into:
- Real linear and real quadratic factors
- Complex linear factors
This usually is obtained by solving Z
n
± 1 = 0
Equation: Z
2
÷ 1 = (Z ÷ 1)(Z + 1)
Equation: Z
2
+ 1 = (Z + i)(Z ÷ i)
Equation: Z
3
÷ 1 = (Z ÷ 1)(Z
2
+ Z + 1)
Equation: Z
3
+ 1 = (Z + 1)(Z
2
÷ Z + 1)
Equation: Z
4
÷ 1 = (Z ÷ 1)(Z + 1)(Z
2
+ 1)
Equation: Z
4
+ 1 = (Z
2
+ 1)
2
÷ 2.Z
2
= ( )( ) 1 Z . 2 Z 1 Z . 2 Z
2 2
+ ÷ + +
Equation: Z
5
÷ 1 = (Z ÷ 1)(Z
4
+ Z
3
+ Z
2
+ Z + 1)
Equation: Z
5
+ 1 = (Z + 1)(Z
4
÷ Z
3
+ Z
2
÷ Z + 1)
Equation: Z
6
÷ 1 = (Z ÷ 1)(Z + 1)(Z
4
+ Z
2
+ 1)
Equation: Z
6
+ 1 = (Z
2
+ 1)(Z
4
÷ Z
2
+ 1)
Equation: Z
n
÷ 1 = (Z ÷ 1)(Z
n ÷ 1
+ Z
n ÷ 2
+ … + Z + 1) if ‘n’ is odd
Equation: Z
n
÷ 1 = (Z ÷ 1)(Z + 1)(Z
n ÷ 2
+ Z
n ÷ 4
+ … + Z
2
+ 1) if ‘n’ is
even
Equation: Z
n
+ 1 = (Z + 1)(Z
n ÷ 1
÷ Z
n ÷ 2
+ … ÷ Z + 1) if ‘n’ is odd
E.g. Factorise Z
6
÷ 1 into quadratic and real factors, hence factorise Z
4
+ Z
2
+ 1.
Luke Cole Page 15
GITIMH3 94107 Complex Numbers Page 16
A
6
. k . 2
sin . i
6
. k . 2
cos Z
t
+
t
= Where, k = 0, … , 5
So the roots are
Z1 = 1
3
sin . i
3
cos Z
2
t
+
t
=
3
. 2
sin . i
3
. 2
cos Z
3
t
+
t
=
Z4 = ÷ 1
3
5
Z
3
. 2
sin . i
3
. 2
cos Z =
t
÷
t
=
2
6
Z
3
sin . i
3
cos Z =
t
÷
t
=
Conjugate pairs
Z2 & Z6
Z3 & Z5
Here,
3
cos . 2 Z Z Z Z 2
2 6 2
t
= + = + …(1)
3
. 2
cos . 2 Z Z Z Z 3
3 5 3
t
= + = + …(2)
|
.
|

\
| t
÷
t
|
.
|

\
| t
+
t
= =
3
sin . i
3
cos
3
sin . i
3
cos Z . Z Z . Z 2 2 6 2
=
2
i .
2
3
.
2
3
4
1
÷
=
4
3
4
1
+
1 Z . Z Z . Z
5 3 6 2
= = …(3)
Since, Z
6
÷ 1 = (Z
2
÷ 1)(Z
4
+ Z
2
+ 1)
= (Z ÷ Z1)(Z ÷ Z2)(Z ÷ Z3)(Z ÷ Z4)(Z ÷ Z5)(Z ÷ Z6)
= (Z ÷ 1)(Z + 1)[Z
2
÷ (Z2 + Z6)Z + Z2.Z6]
[Z
2
÷ (Z3 + Z5)Z + Z3.Z5] …(4)
Sub (1), (2) & (3) into (4)

( )( ) |
.
|

\
|
+
t
÷ |
.
|

\
|
+
t
÷ + ÷ = ÷ 1 Z .
3
. 2
cos . 2 Z 1 Z .
3
cos . 2 Z 1 Z 1 Z 1 Z
2 2 6
Luke Cole Page 16
GITIMH3 94107 Complex Numbers Page 17
Triangular Inequality
E.g. Proof that ¦Z1 + Z2¦ s ¦Z1¦ + ¦Z2¦
A
Here, OA = BC = ¦Z1¦ & AC = OB = ¦Z2¦
So, we can assume in AOAC
OA + AC > OC
¦Z1 + Z2¦ < ¦Z1¦ + ¦Z2¦
The inequality is equal when
arg Z1 = arg Z2
¦Z1 + Z2¦ s ¦Z1¦ + ¦Z2¦
Luke Cole Page 17
C(Z
1
+ Z
2
)
B(Z
2
)
A(Z
1
)
O
GITIMH3 94107 Complex Numbers Page 18
Geometric Representation of Complex Number’s
Addition:
Proof:
So, mid-point of AB:
|
.
|

\
| + +
=
2
y y
,
2
x x
M
2 1 2 1
Therefore the co-ordinates of C must be:
|
.
|

\
| + +
¬
2
y y
,
2
x x
. 2 C
2 1 2 1
( )
2 1 2 1
y y , x x C + + ¬
Hence, point C corresponds to the sum of the complex numbers Z
1
and Z
2
:
Z1 + Z2 = (x1 + i.y1) + (x2 + i.y2)
= (x1 + x2) + i(y1 + y2)
Subtraction:
Proof:
From the parallelogram OBCD the co-ordinates of C are:
( )
1 2 1 2
y y , x x C ÷ ÷ ¬
Hence, point C corresponds to the subtraction of the complex numbers Z
1
and Z
2
:
Z2 ÷ Z1 = (x2 + i.y2) ÷ (x1 + i.y1)
= (x2 ÷ x1) + i(y2 ÷ y1)
Luke Cole Page 18
C(Z
1
+ Z
2
)
B(Z
2
)
A(Z
1
)
O
B(Z
2
)
C(Z
2
÷ Z
1
)
A(Z
1
)
O
D(÷ Z
1
)
Z1 = x1 + i.y1
Z2 = x2 + i.y2
Z1 + Z2 = (x1 + x2) + i(y1 + y2)
OB¦¦AC
BC¦¦OA
Z1 = x1 + i.y1
Z2 = x2 + i.y2
Z2 ÷ Z1 = (x2 ÷ x1) + i(y2 ÷ y1)
CB¦¦DA
CD¦¦BO
GITIMH3 94107 Complex Numbers Page 19
Product:
Proof:
Here, arg (Z1.Z2) = u1 + u2
And since, AOAB¦AOCB:
OA
OC
OB
OP
=
1
r
r
OP
2
1
=
OP = r1.r2
Hence, point P corresponds to the product of the complex numbers Z
1
and Z
2
:
Z1.Z2= r1.r2.cis (u1 + u2)
Luke Cole Page 19
P(Z
1
.Z
2
)
C(Z
2
)
u
1
r
2
u
2
r
1
B(Z
1
)
u
1
O A
Z1 = x1 + i.y1
Z2 = x2 + i.y2
Z1.Z2= r1.r2.cis (u1 + u2)
ZOCD = ZOAB
AOAB¦AOCB
Note:
Multiplication of ‘i’ corresponds to a rotation in the anti-clockwise
direction through an angle of
t
/2.
i.e. i ¬ arg
t
/2
i
2
¬ arg t
i
3
¬ arg ÷
t
/2
i
4
¬ arg 0
GITIMH3 94107 Complex Numbers Page 20
The Locus of C.N.
Equation: ¦Z ÷ e¦ = r or ( )( )
2
r Z Z = e ÷ e ÷
e = Centre
r = radius
E.g. (1) Find the locus of ¦Z¦= 3
A From, ¦Z¦= 3
¦Z¦= ¦x + i.y¦ =
2 2
y x +
So,
2 2
y x +
= 3
x
2
+ y
2
= 9
Here, centre (0, 0) radius 3
E.g. (2) Find the locus of ¦Z ÷ 2 + i¦ < 4
A Since, Z = x + i.y
Now, ¦x + i.y ÷ 2 + i¦ < 4
¦(x ÷ 2)+ i(y + 1)¦ < 4
( ) ( ) 4 1 y 2 x
2 2
< + + ÷
(x ÷ 2)
2
+ (y + 1)
2
< 16
Here, centre (2, ÷ 1) radius 4
E.g. (3) Sketch the region defined by 0 s arg Z s
t
/3
A
Luke Cole Page 20
3

t/3
Note:
Exclude origin, as it is
not an angle but a point
GITIMH3 94107 Complex Numbers Page 21
E.g. (4) Find the locus of e if
Z
1 Z ÷
= e
is given by ¦Z¦ = 2
A Make Z the subject,
e ÷
=
1
1
Z
Now,
e ÷
=
1
1
Z
1 = 2.¦1 ÷ e¦
1 = 2.¦1 ÷ (x + i.y)¦ = ( )
2 2
y x 1 . 2 + ÷
(1 ÷ x)
2
+ y
2
= ¼
Luke Cole Page 21

Sign up to vote on this title
UsefulNot useful